"Bumpy" ride for the female cyclist: A rare case of perineal nodular induration, the ischial hygroma. (2020) - Norman, Mackenzie; Vitale, Kenneth
Highlights: PNI is a pseudoneoplastic lesion caused by repetitive microtrauma. Shearing in perineal fascia stimulates fibroblastic proliferation. Reported almost exclusively in males, it can occur in females and is underdiagnosed. Cyclists and any saddle sport athletes (even seated lawnmowing) are at risk. Treatment is to remove the trigger; surgery can be considered in refractory cases. Abstract: Introduction: Cycling is known to cause groin pain, typically adductor/hamstring strains and "saddle sores" (skin abrasion, ulceration and/or folliculitis). Rarely does it result in pathological mesenchymal lesions. Presentation of case: We report a case of a 52-year-old female avid cyclist with chronic groin pain. Activity alteration, bike fit, and saddle modification did not ameliorate her symptoms. MRI revealed no hamstring or bony abnormality but demonstrated low T1/high T2 signal in the right perineum inferior to the ischial tuberosity. Discussion: Perineal nodular induration, or "cyclist's nodule, " is a reactive fibroblastic and myofibroblastic pseudotumor almost exclusively reported in male cyclists. PNI can become so nodular that it has even been referred to as an accessory testicle or "the cyclist's third testicle." Conclusion: We report an unusual case of PNI in a female cyclist and review the differential diagnosis of non-infectious soft tissue perineal pain in cyclists. Clinicians should be aware of this rare condition to avoid confusion with other mesenchymal lesions.